Sustainability: How Stakeholder Perceptions Differ from Corporate Reality - Peloza, John; Loock, Moritz; Cerruti, James; Muyot, Michael (California management review, 2012)
A strong reputation is widely acknowledged to be the most valuable asset of a firm, and sustainability has become an important component of corporate reputation. Many stakeholders, from customers to investors to employees to purchasing managers, report that sustainability is an important factor in their decision-making processes. However, sustainability messages have become ubiquitous–almost table stakes–for most large firms. In such an active marketplace, especially for firms who have not pursued leadership positions, it is difficult for companies to use sustainability to create meaningful differentiation from competitors and thus benefit from their investments. There is often a major gap between stakeholder perceptions and firm performance. Firms that integrate sustainability into their culture and business practices are better able to integrate sustainability messaging into mainstream communications.